Role of extracytoplasmic function sigma factor PG1660 (RpoE) in the oxidative stress resistance regulatory network of Porphyromonas gingivalis - Dou, Y. (Mol Oral Microbiol, 2017)
In Porphyromonas gingivalis, the protein PG1660, composed of 174 amino acids, is annotated as an extracytoplasmic function (ECF) sigma factor (RpoE homologue-σ24). Because PG1660 can modulate several virulence factors and responds to environmental signals in P. gingivalis, its genetic properties were evaluated. PG1660 is co-transcribed with its downstream gene PG1659, and the transcription start site was identified as adenine residue 54-nucleotides upstream of the ATG translation start codon. In addition to binding its own promoter, using the purified rPG1660 and RNAP core enzyme from Escherichia coli with the PG1660 promoter DNA as template, the function of PG1660 as a sigma factor was demonstrated in an in vitro transcription assay. Transcriptome analyses of a P. gingivalis PG1660-defective isogenic mutant revealed that under oxidative stress conditions 176 genes including genes involved in secondary metabolism were downregulated more than two-fold compared with the parental strain. The rPG1660 protein also showed the ability to bind to the promoters of the highly downregulated genes in the PG1660-deficient mutant. As the ECF sigma factor PG0162 has a 29% identity with PG1660 and can modulate its expression, the cross-talk between their regulatory networks was explored. The expression profile of the PG0162PG1660-deficient mutant (P. gingivalis FLL356) revealed that the type IX secretion system genes and several virulence genes were downregulated under hydrogen peroxide stress conditions. Taken together, we have confirmed that PG1660 can function as a sigma factor, and plays an important regulatory role in the oxidative stress and virulence regulatory network of P. gingivalis.